Building a new technological relationship and rivalry : US-China Relations in the Aftermath of COVID (2020)
Containing COVID-19 requires opposite moves. Stopping the virus requires radical separation—of the sick and the healthy, of communities stricken and those spared, of nations whose borders are ordinarily open to people and goods. In a better world, this radical separation would be paired with intense cooperation—cooperation in finding and distributing a vaccine, restarting the world economy, and pooling resources to prevent future outbreaks. COVID-19 marks one of the first times that we as a species have faced a sudden global crisis with modern communications linking us seamlessly together. It could easily be a unifying moment